The Influence of Communication and Resources on the Implementation of Deep Learning Policy in Penajam District Elementary School - Badru, Iis Purwanty; Hazin, Mufarrihul; Khamidi, Amrozi (Journal of English Language and Education, 2026)
This study aims to analyze the influence of communication and resources on the implementation of in-depth learning policies in elementary schools in Penajam District. Previous studies on educational policy implementation have generally emphasized structural and administrative factors; however, limited research has specifically examined how communication processes and resource availability jointly influence the implementation of in-depth learning policies at the elementary school level, particularly in regional contexts. This gap highlights the need for empirical investigation into the role of these factors in supporting effective policy implementation in schools. The study used a quantitative approach with an associative (correlational) design to statistically test the relationship and influence between variables. The study population consisted of all 289 public elementary school teachers in Penajam District who implemented in-depth learning. The research sample consisted of 168 teachers determined using a probability sampling technique with the Slovin formula at a 5% error rate. Data collection was carried out through a survey method using a questionnaire that had been tested for validity and reliability. Data analysis was carried out through descriptive statistics, classical assumption tests, multiple linear regression analysis, and hypothesis testing using t-tests, F-tests, and coefficients of determination. The results showed that communication and resources had a positive and significant influence on the implementation of in-depth learning policies. Partially, communication had the most dominant influence with a beta coefficient value of 0.631, while resources had a positive influence with a beta coefficient value of 0.184. Simultaneously, both variables had a significant influence with a calculated F value of 65.102 and a significance level of 0.000. The coefficient of determination of 43.4% indicates that communication and resources partially explain the variation in the implementation of immersive learning policies in elementary schools. This finding underscores the importance of effective policy communication and adequate resource support in enhancing the success of immersive learning implementation in elementary schools.